2016
DOI: 10.1159/000448444
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicine Use Among Chronically Ill Adolescents from 2 German Birth Cohorts

Abstract: Background: Pediatric use of complementary and alternative medicine (CAM) is popular in Europe, and utilization may be even more prevalent in chronically ill children/adolescents. This study's aim is to assess CAM use among adolescents with chronic conditions. Methods: Data on drug utilization (past 4 weeks) and consultation with CAM providers (past year) were collected using a self-administered questionnaire from 4,677 adolescents from the German GINIplus/LISAplus birth cohorts. All reported drugs were classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The variability in treatment procedures together with the chronicity of the disease might stimulate an interest in complementary or alternative medications and treatments (CAM) [2]. Although CAM is not supported by scientific evidence [3, 4], it has been in great demand for decades [5] and shown to be more frequently used in chronic patients [6]. CAM use in dermatology is believed to be most frequent among AD patients but other diseases, including psoriasis and acne, are also associated with prevalent CAM use [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…The variability in treatment procedures together with the chronicity of the disease might stimulate an interest in complementary or alternative medications and treatments (CAM) [2]. Although CAM is not supported by scientific evidence [3, 4], it has been in great demand for decades [5] and shown to be more frequently used in chronic patients [6]. CAM use in dermatology is believed to be most frequent among AD patients but other diseases, including psoriasis and acne, are also associated with prevalent CAM use [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, studies have shown that vulnerable children, such as those with chronic, recurrent or incurable conditions that are difficult to manage or children taking prescription medication [31], are more likely to seek CAM alternatives than others [32][33][34]. Rates of children with such conditions are estimated to be greater than 50% of the total of children using CAM, with oncology patients leading the list with 63% [35,36].…”
Section: Paediatric Population and Cammentioning
confidence: 99%
“… 1 Even though CAM often lacks scientific evidence to support it, 2 , 3 it has been used for decades 4 and has been demonstrated to be used more often by patients with chronic conditions. 5 Throughout the previous few decades, CAM has attained more attention and has been more frequently used by patients worldwide. 6 , 7 The rate of alternative medicine utilization differs across regions and ranges from 5 to 74.8% in the overall population.…”
Section: Introductionmentioning
confidence: 99%